3. Nature, Religion, and Imagination: Comments on Images of History - Clewis, Robert R. (History and theory, 2018)
After sharing some reflections, I raise three questions. The first asks about the role of nature and reason according to Kant's teleological history, and the extent to which Kant's essays written before the Critique of the Power of Judgment (1790) are “dogmatic,” as his phrase “aim of nature” might suggest. The second asks about Kant's “impure” ethics and the role of religion. What would Kantian religion look like today? The last question concerns the relation between images and ideas—a thornier issue than Kant's initial definitions of imagination and reason would seem to suggest.